On the persistence of dishonesty - Stefania Bortolotti; Felix Kölle; Lukas Wenner (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
In social and economic interactions, individuals often exploit informational asymmetries and behave dishonestly to pursue private ends. In many of these situations the costs and benefits from dishonest behavior do not accrue immediately and at the same time. In this paper, we experimentally investigate the role of time on dishonesty. Contrary to our predictions, we find that neither delaying the gains from cheating, nor increasing temporal engagement with one's own unethical behavior reduces the likelihood of cheating. Furthermore, allowing for a delay between the time when private information is obtained and when it is reported does not affect cheating in our experiment.
Keywords: C91; D82; D91; 330; Dishonesty; cheating; delay; discounting; experiment